2003
DOI: 10.2514/atcq.11.4.277
|View full text |Cite
|
Sign up to set email alerts
|

A General Approach to Equity in Traffic Flow Management and Its Application to Mitigating Exemption Bias in Ground Delay Programs

Abstract: A primary objective of the FAA's ATM functions is to provide fair and equitable access to the National Air Space. Traditionally, the FAA has interpreted fairness as prioritizing flights on a "first-come, first-served" basis. The allocation procedures introduced under Collaborative Decision Making (CDM), however, represent a departure from this paradigm: allocations are based on carriers' original flight schedules. Yet in spite of these changes, the concept of fairness under CDM is largely left implicit in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 8 publications
0
34
0
Order By: Relevance
“…And it is the responsibility of each individual airline to decide how it will use its allocated share of capacity at each part of the system. This is a somewhat simplistic description of what, in practice, is a complicated process that employs several types of distributed decision-making techniques, such as rationing by schedule (RBS) and schedule compression-see Wambsganss (1996) and Vossen et al (2003) for details.…”
Section: Air Traffic Flow Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…And it is the responsibility of each individual airline to decide how it will use its allocated share of capacity at each part of the system. This is a somewhat simplistic description of what, in practice, is a complicated process that employs several types of distributed decision-making techniques, such as rationing by schedule (RBS) and schedule compression-see Wambsganss (1996) and Vossen et al (2003) for details.…”
Section: Air Traffic Flow Managementmentioning
confidence: 99%
“…Examples of some topics, along with occasional recent references, include: identifying (as an airline) flights that should be cancelled or delayed (and by how much) in connection with GDPs, recovering (as an airline) from irregular operations (cf. §2) resulting from GDPs or other ATFM interventions, ensuring equity of access to airports and ATM resources (Vossen et al 2003), collaborative routing of aircraft through congested airspace (Ball et al 2002), introducing bartering and possibly market-based mechanisms in the allocation of airport slots (Vossen andBall 2001, Hall 1999), and developing efficient simulation environments for the testing of alternative ATFM strategies.…”
Section: Air Traffic Flow Managementmentioning
confidence: 99%
“…A future research direction is to a study the Rule's impact on airlines with different network structures, such as, international carriers, regional carriers, legacy carriers, and low-cost carriers. It has been shown that smaller aircraft on short-haul flights are assigned disproportionally more ground delay time (Vossen et al, 2003). Thus, it would be interesting to examine if regional airlines incur disproportionately more delay as a result of the Rule, thereby introducing inequitable impacts.…”
Section: Conclusion and Future Research Directionsmentioning
confidence: 99%
“…We follow the approach of Vossen et al (2003), where the inequity of a given allocation is defined as its deviation from an ideal allocation, which we define as the pure RBS allocation, meaning RBS without any discretionary exemptions. Vossen et al (2003) and Vossen and Ball (2006a) provide strong justification for this choice. For each flight k f , let a" k , denote the RBS slot assignment.…”
Section: Equity Considerations and A Practical Approachmentioning
confidence: 99%
“…However, preserving equity among the competing airspace users has also emerged as a fundamental performance criterion (see Vossen et al 2003, Vossen andBall 2006a). Under the Collaborative Decision Making (CDM) initiative, the ration-by-schedule (RBS) algorithm has been accepted as the standard for equitable allocation.…”
Section: Introductionmentioning
confidence: 99%